From “Woman as Thing” to a “Subject-In-Process”: The Dynamics of Courtly Love in Charlotte Lennox’s The Female Quixote (1752) - Ayesha Siddiqa (NUML Journal of Critical Inquiry)
Slavoj Žižek’s psychoanalytic analysis of “courtly love” concludes that the courtly image of the Knight’s subservience to his Lady actually masks the reality of male domination; however, Žižek’s own analysis seems complicit in the same problematic. Whereas courtly love provides a semblance of agency to the woman, in assuming the male partner as the subject from whose vantage the relationship is theorized, Žižek’s analysis strips the woman of any subjectivity or agency by rendering her an absolute object, a radical Otherness, a monster, and an automaton. While Žižek painstakingly represents the male-subject as the victim-agent in being the director of the masochistic performance, the female is rendered a perpetrator-object who despite enacting the terms of the same contract is termed an inhuman partner and hence a sadist. This lack of complex theorization of the Lady that renders her absolute evil reinforces conventional representation of femininity as evil. Besides, by declaring an impasse in feminism for its tendency to deny women ‘femininity’, Žižek, while bemoaning the inescapability of the asymmetrical love relationship ends up reifying it. While Žižek’s analysis writes the Lady off as a vacuum, Charlotte Lennox’s The Female Quixote (1752) provides an interesting alternative for theorizing courtly love from the vantage of the Lady via the protagonist, Arabella. A suitable framework for understanding Arabella’s investment in the conventions of courtly love can be found in Julia Kristeva’s psychoanalytical model that allows for reconceiving the Lady in courtly love as a subject. While developing on the scholarship that explores the novel’s negotiation of the gendered eighteenth-century English society, I argue that Arabella’s delusional immersion in romances signifies her proximity to the semiotic chora given her preoedipal maternal severance. As such, her preference of the “feminine” form of romance, reflective of the subversive force of the semiotic, represents Arabella’s defiance of the rational, masculine, novelistic discourse of the eighteenth-century symbolic.